Challenging the safety and efficacy of topically applied chlorogenic acid, apigenin, kaempferol, and naringenin by HET-CAM, HPLC-TBARS-EVSC, and laser Doppler flowmetry - Ruscinc, Nadia; Massarico Serafim, Ricardo Augusto; Almeida, Cíntia; Rosado, Catarina; Baby, André Rolim (Frontiers in Chemistry, 2024)
The integumentary system, a vital organ, constitutes a multifaceted barrier against pathogens and environmental factors, crucial for maintaining homeostasis. Intrinsic and extrinsic factors can accelerate skin aging and compromise its homeostatic functions and solar rays, particularly ultraviolet (UV) radiation, pose a significant risk for skin cancer. Polyphenols are molecules that donate hydrogen or electrons, preventing the oxidation of substances, such as lipids, or the formation of inflammatory mediators by cyclooxygenase enzymes. This study explored the in vitro safety, by HET-CAM (hen’s egg test on chorioallantoic membrane), and protective effects of polyphenols (chlorogenic acid, apigenin, kaempferol, and naringenin) against stratum corneum UV-induced lipid peroxidation using an innovative method, the HPLC-TBARS-EVSC (high-performance liquid chromatography–thiobarbituric acid reactive substances–ex vivo stratum corneum), and a stress test using methyl nicotinate and laser Doppler flowmetry to establish in vivo the samples’ topical anti-inflammatory ability. An aqueous gel containing 0.1% w/w of each polyphenol was formulated using ammonium acryloyldimethyltaurate/VP copolymer. Through the utilization of the HET-CAM assay for in vitro safety assessment, chlorogenic acid, apigenin, kaempferol, and naringenin were classified as non-irritating active ingredients. This classification was based on their lack of adverse reactions within the vascularization of the chorioallantoic membrane. To assess the protective capabilities of four polyphenols against lipid peroxidation in the stratum corneum, the HPLC-TBARS-EVSC protocol was conducted. It was observed that only naringenin exhibited a significant reduction in epidermal lipoperoxidation, indicating superior anti-radical potential. Conversely, chlorogenic acid, apigenin, and kaempferol displayed a pro-oxidant profile under the specified test conditions. The laser Doppler flowmetry suggested the anti-inflammatory potential of naringenin, kaempferol, and chlorogenic acid, with naringenin showing superior efficacy involving all parameters quantified. Naringenin emerged as the only polyphenol capable of reducing the intensity of the inflammatory response induced by methyl nicotinate solution in the participants, compared to the blank gel and the untreated area. This comprehensive investigation underscores the diverse protective roles of polyphenols in skin health, emphasizing naringenin’s notable anti-radical and anti-inflammatory properties.